Novel Opportunity to Reverse Antibiotic Resistance: To Explore Traditional Chinese Medicine With Potential Activity Against Antibiotics-Resistance Bacteria - Su, Ting; Qiu, Ye; Hua, Xuesi; Ye, Bi; Luo, Haoming; Liu, Da; Qu, Peng; Qiu, Zhidong (Frontiers in Microbiology, 2020)
Antibiotic resistance is becoming significantly prominent and urgent in clinical practice with the increasing and wide application of antibacterial drugs. However, developing and synthesizing new antimicrobial drugs is costly and time-consuming. Recently, researchers shifted their sights to traditional Chinese medicine (TCM). Here, we summarized the inhibitory mechanism of TCM herbs and their active ingredients on bacteria, discussed the regulatory mechanism of TCM on antibiotic-resistant bacteria, and revealed preclinical results of TCM herbs and their active components against antibiotic-resistant bacteria in mouse models. Those data suggest that TCM herbs and their effective constituents exhibit potential blockage ability on antibiotic-resistant bacteria, providing novel therapeutic ideas for reversing antibiotic resistance.